Role of Known Transient Receptor Potential Vanilloid Channels in Modulating Cardiac Mechanobiology - Miller, Michael; Koch, Sheryl E.; Veteto, Adam; Domeier, Timothy; Rubinstein, Jack (Frontiers in Physiology, 2021)
The transient receptor potential (TRP) channels have been described in almost every mammalian cell type. Several members of the Vanilloid (TRPV) subtype have been found to play important roles in modulating cardiac structure and function through Ca2+ handling in response to systemic and local mechanobiological cues. In this review, we will consider the most studied TRPV channels in the cardiovascular field; transient receptor potential vanilloid 1 as a modulator of cardiac hypertrophy; transient receptor potential vanilloid 2 as a structural and functional protein; transient receptor potential vanilloid 3 in the development of hypertrophy and myocardial fibrosis; and transient receptor potential vanilloid 4 in its roles modulating the fibrotic and functional responses of the heart to pressure overload. Lastly, we will also review the potential overlapping roles of these channels with other TRP proteins as well as the advances in translational and clinical arenas associated with TRPV channels.